FAKTOR-FAKTOR YANG MEMPENGARUHI WAJIB PAJAK ORANG PRIBADI DALAM MENGIKUTI TAX AMNESTY PADA KANTOR PELAYANAN PAJAK PRATAMA KUPANG - Manubulu, Herry Aprilia; Cardoso, Isabel (Politeknik Negeri Ambon, 2023)
This study aims to determine the effect of socialization of taxation, tax rates, tax sanctions, and ease of application on the wishes of individual taxpayers to participate in tax amnesty at KPP Pratama Kupang. The type of research used was a survey. The population for this study was WPOP who had participated in tax amnesty volumes I and II at KPP Pratama Kupang, and sampling used an incidental/accidental sampling technique to obtain 50 WPOP used as research samples. The data collection technique used a questionnaire which was then analyzed using multiple linear regression analysis to analyze the influence of tax socialization variables, tax rates, tax sanctions, and ease of application. The results of the study show that tax socialization hurts the desire of taxpayers to participate in tax amnesty, tax rates have a positive influence on the desire of taxpayers to participate in tax amnesty, tax sanctions have a positive effect on the desire of taxpayers to participate in tax amnesty and the ease of application has a positive effect on the willingness of taxpayers to participate in tax amnesty